Preparation of room-temperature self-healing elastomers with high strength based on multiple dynamic bonds. (5th August 2021) - Zhang, Wencong; Wang, Minhui; Zhou, Jiahui; Sheng, Yeming; Xu, Min; Jiang, Xiaolin; Ma, Yuanhao; Lu, Xun
Graphical abstract: Highlights: Aromatic disulfide bonds give elastomer room-temperature self-healing capacity. Multiple hydrogen bonds enhance the dynamic characteristics of the chain. The coordination bonds are readily adjustable. The synergy of multiple dynamic bonds endows the elastomer with admirable properties. Abstract: As far as the self-healing elastomers are concerned, there is a contradiction between mechanical strength and self-healing performance because it's hard to acquire strong intermolecular interaction and flexible segments motion concurrently. How to prepare room-temperature self-healing elastomers with high strength remains an enormous challenge. Herein, we synthesized room-temperature self-healing thermoplastic polyurethanes (TPUs) incorporated with multiple hydrogen bonds, reversible disulfide bonds and coordination bonds simultaneously. The prepared elastomers exhibit a tensile strength of over 16.1 MPa and a fracture strain of 771%, which are robust in comparison to most previous reports. The multiple dynamic bonds endow the elastomers with a high self-healing efficiency (94%) within 24 h at room temperature. The self-healing mechanism was expounded from the perspective of the aggregate structure such as the degree of aggregation, the degree of microphase separation and molecular dynamics. It can be calculated by the dynamic mechanical analysis that the activation energy of the target elastomer is lower than that of samples without dynamic interactions, which is of advantage to self-healing properties.